Successes in sexual health communications development, programmatic implementation and evaluation in the Torres Strait region 2006 to 2012 - Patricia S. Fagan; Heather K. Robertson; Alisa E. Pedrana; Alexandra Raulli; Alan A. Crouch (Elsevier, 2015)
Abstract Objective: To evaluate the Indigenous sexual health promotion program in the Torres Strait 2006-2012 that culminated in an education‐entertainment radio drama, Kasa Por Yarn (KPY). Methods: A mixed methods approach applied to unpublished program documents and program‐derived peer‐reviewed publications was utilised. Results: Early initiatives established a strong partnership with Torres Strait Islander stakeholders. Significant community engagement throughout ensured a positive process. Telephone survey data (n=100, TSI, 15-24 years) found: 95% had heard of KPY and 80% listened to 2 or more episodes (reach); 86% recalled storylines/characters (recall); and 54% talked about KPY to family/friends (resonance). There was improvement in sexual health knowledge scores (p<0.00) in the 15-19‐year‐old Torres Strait Islander population between 2007 and 2012. The 2012 15-24‐year‐old population exposed to KPY had higher sexual health knowledge scores compared with those unexposed (p=0.02). Conclusions: This is an uncommon comprehensive evaluation of population‐based sexual health communications strategies delivered over years in a remote Australian setting. The findings are encouraging but demonstrate that positive shifts take time and are incremental. Implications: In addition to clinical strategies, strategic and sustained investment in sexual health promotion expertise that leads community partnership and program development is required to reduce youth risk and prevent HIV/AIDS in remote populations.